2021
DOI: 10.1016/j.clnesp.2021.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of vitamin D deficiency on COVID-19

Abstract: Background and aims COVID - 19 has emerged as a global pandemic affecting millions of people. Vitamin D deficiency is one of the risk factors for increased susceptibility to COVID-19. This study aimed to examine the correlation between the prevalence of vitamin D deficiency and COVID - 19 infection and mortality rates among the adult population in European and Asian continents. Methods Prevalence of vitamin D deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 64 publications
1
7
0
1
Order By: Relevance
“…It was noted early in the pandemic that there was some correlation between COVID‐19 mortality by country and historical vitamin D status [19]. A more recent study across 47 European and Asian countries has confirmed this association (r = 0.35; p = 0.016) [20].…”
Section: Methodsmentioning
confidence: 94%
“…It was noted early in the pandemic that there was some correlation between COVID‐19 mortality by country and historical vitamin D status [19]. A more recent study across 47 European and Asian countries has confirmed this association (r = 0.35; p = 0.016) [20].…”
Section: Methodsmentioning
confidence: 94%
“…and vitamin D by 9% (OR ¼ 0.91; p < 0.001) [37]. As vitamin D deficiency has been associated with COVID-19 mortality rate in the Asian region, vitamin D supplementation could have a vital role in the prevention or treatment of the disease [38,39]. Accordingly, vitamin D supplementation was administered among elderly patients in France with COVID-19 and were less likely to exhibit severity (OR ¼ 0.46; 95% CI, 0.01e0.81; p ¼ 0.033) [40].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of observational studies indicate that low 25-hydroxy-cholecalciferol (25(OH)D) concentrations are associated with a higher risk of infection and hospitalisation [ 16 , 17 ]. A comparison of European and Asian countries using infection and mortality data from the Worldometer ( , assessed on 31 December 2020) found that vitamin D deficiency is associated with increased infection and mortality rates [ 18 ]. Those at particular risk of COVID-19 infection associated with low 25(OH)D include the elderly [ 19 ], black women in the US [ 20 ], pregnant women [ 21 ] or patients with relevant co-morbidities such as chronic kidney disease [ 22 ].…”
Section: Introductionmentioning
confidence: 99%